2020
DOI: 10.1097/md.0000000000023249
|View full text |Cite
|
Sign up to set email alerts
|

Intrajejunal vs oral levodopa-carbidopa therapy in Parkinson disease

Abstract: Levodopa-carbidopa intestinal gel (LCIG) is a method of continuous administration of levodopa – the standard treatment in Parkinson disease (PD, a neurodegenerative disorder characterized by resting tremor, rigidity, gait impairment, and bradykinesia), thought to reduce the short-life and pulsatile problems of oral administration. We aimed to study the effects of Levodopa-Carbidopa therapy in 2 separate groups: one with intrajejunal administration of Levodopa-Carbidopa gel and the second with oral therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Caffein, as an A2A antagonist, may be a factor delaying the onset of LID [ 111 ]. The N-of-1 study on nicotine use demonstrated a significant effect of nicotine on the occurrence of LID compared to a placebo [ 112 ].…”
Section: Resultsmentioning
confidence: 99%
“…Caffein, as an A2A antagonist, may be a factor delaying the onset of LID [ 111 ]. The N-of-1 study on nicotine use demonstrated a significant effect of nicotine on the occurrence of LID compared to a placebo [ 112 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the therapeutic options for advanced PD, only Levodopa-carbidopa intestinal gel (LCIG) and deep brain stimulation (DBS) are currently available in Romania. The LCIG has gained increased attention from the Romanian researchers, with the publication of 11 studies [114,118,120,125,126,132,[138][139][140]142,143]. However, no studies on DBS were published in Romania, possibly due to the limited availability of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric emptying is a rate-limiting step for orally administered levodopa, which is absorbed in the proximal small intestine 29 . Thus, gastric motility issues can lead to fluctuating plasma concentrations of levodopa, producing motor fluctuations 30 . The levodopa/carbidopa intestinal gel infusion system provides continuous carbidopa and levodopa infusion through a percutaneous endoscopic gastrojejunostomy (PEG-J) tube via a portable infusion pump 30 .…”
Section: Levodopa/carbidopa Intestinal Gel Infusionmentioning
confidence: 99%
“…30 The levodopa/carbidopa intestinal gel infusion system provides continuous carbidopa and levodopa infusion through a percutaneous endoscopic gastrojejunostomy (PEG-J) tube via a portable infusion pump. 30 An advantage of levodopa/carbidopa intestinal gel infusion over orally provided levodopa is that it can deliver continuous rather than pulsatile medication throughout the day, and delivery of the levodopa bypasses the stomach to the jejunum, avoiding problems that arise with gastric emptying issues. 26 By doing so, this stabilizes the motor fluctuations during the awake period, as plasma levodopa concentrations reach a steady state.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation